EVALUASI PRETEST DAN POSTTEST PESERTA PELATIHAN PRAKTIK BUDIDAYA JAMUR TIRAM DESA TASIWALIE KABUPATEN PINRANG - Nur Rahmah Wahyuddin; Azwar Azwar; Riska Arnas; Abdul Kadir (Universitas Ichsan Sidenreng Rappang, 2024)
This study focuses on evaluating the pretest and posttest results of participants in practical training for oyster mushroom cultivation in Tasiwalie Village, Pinrang Regency. The training aims to enhance the skills and knowledge of participants in mushroom cultivation, with a specific focus on the context of the Lowita Mushroom business group. This research utilizes pretest and posttest as measurement tools to assess the effectiveness of the training program. The methodology involves administering pretests to evaluate participants' baseline knowledge and skills before the training. Subsequently, practical training in oyster mushroom cultivation is conducted. Posttests are then administered to measure participants' improvement and understanding after completing the training. The initial findings from distributed questionnaires indicate an analysis of pretest and posttest scores, revealing a significant change in participants' scores. Specifically, the pretest scores show an average increase of 52.10, while the posttest scores show an average increase of 67.75, representing approximately a 30% average improvement among the 20 respondents. The positive impact of the training on the development of mushroom cultivation skills within the context of the Lowita Mushroom business group is evident. This research contributes to a broader understanding of the effectiveness of practical training programs in enhancing specific skills, particularly in the field of mushroom cultivation. The results emphasize the importance of training initiatives in fostering economic development and improving the well-being of the local community, with implications for sustainable practices in the Tasiwalie Village area. Further analysis and long-term follow-up are recommended to assess the sustainable impact of the training on participants and the overall development of the Lowita Mushroom business group in Tasiwalie Village, Pinrang Regency.